Efektifitas Pelayanan Administrasi kepada Mayarakat - Kodrat Rippi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Basically, every human being always needs service. All people have the right to receive good and quality services from the government regardless of race, ethnicity, position and other people who are equal without differences between individuals. This is as stated in the symbol of the struggle and protection of the Indonesian nation (Pancasila), the fifth principle which states social justice for all Indonesian people. The performance capability of Village officials in providing administrative services to the people of Kamiri Village, Masamba District. Factors that hinder the performance of Village officials in providing services to the people of Kamiri Village, Masamba District. The factor inhibiting the performance of Village officials in providing administrative services to the community in Kamiri Village, Masamba District is the leadership factor, where the village head as the leader of Village government administration is less assertive. Efforts made by village officials to overcome obstacles to the performance of village officials in providing administrative services in Kamiri village, Masamba subdistrict are by utilizing technology.